Numerical Classification of some Soils of Bhabar Forest Region of Uttar Pradesh - Kumar, Suman; Sharma, A. K. (Indian Forester, 1992)
Numerical classification of 8 forest soils belonging to orders Entisol, Inceptisol and Mollisol of Bhabar region of Nainital District in Uttar Pradesh was done. The taxonomic structure worked out using dissimilarity coefficients was presented using the clustering technique of Unweighted Pair Group Method using Arithmetic averages (UPGMA). The grouping of soils on the basis of numerical classification is in general, in conformity with their classification according to USDA Taxonomy. Departures from this general observation suggest a re-examination of existing taxonomic classification.